Using KAHOOT for interactive English Learning: A review of Current Literature - ridho kurniawan (STKIP Muhammadiyah Muara Bungo, 2020)
Use of technology has become an important part of the learning process in and out of the classroom. Every language class usually uses some form of technology. Technology has been used to both help and improve language learning. Technology enables teachers to adapt classroom activities, thus enhancing the language learning process.Technology continues to grow its importance as a tool to help teachers facilitate language learning for theirlearners. It discussed different attitudes which support English language learners to increase their learning skills through using technologies. This can make students passionate about accepting the material delivered by educators so that the effectiveness of learning can be achieved. And can making Classroom fun and not boring when we use technology in study and activities in classroom and Kahoot is present as a learning application to foster motivation and enthusiasm for learners to create conducive classroom conditions for the achievement of the effectiveness of learning.Use of the Kahoot platform used was very suitable to be used in creating interactive and fun learning.